1990
DOI: 10.1037/0022-3514.59.3.501
|View full text |Cite
|
Sign up to set email alerts
|

Similarity of outcomes, interdependence, and conflict in dating relationships.

Abstract: Dating couples (N = 59) participated in a longitudinal study of hypotheses derived from interdependence theory. Whether each partner's activity preferences and similarity of preferences, weighted by liking, would predict joint activity participation was examined. Preferences explained participation better than similarity, and own preferences predicted better than other's preferences. We hypothesized that conflict would increase with the strength of preferences but would decrease with similarity. The hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(62 citation statements)
references
References 19 publications
(19 reference statements)
4
55
1
1
Order By: Relevance
“…The SLC is a 20-item measure tapping both the ' 'liking'' and ' "competence'' components of global self-esteem, and the SAQ is a 15-item measure tapping the respondent's self-perceived intelligence, social competence, artistic /musical ability, athleticism, and attractiveness; the certainty with which the respondent holds these five self-views; and the importance of these self-views to the respondent. Finally, targets completed the Activity Preferences Questionnaire (APQ; Surra & Longstreth, 1990), a 37-item measure that requires respondents to rate the extent to which they enjoy various activities (e.g., cleaning their rooms, going to a bar, playing board games, etc.). 2 Perceivers completed the same questionnaires as the targets but were instructed to "answer each questionnaire the way you think your partner would answer."…”
Section: Methodsmentioning
confidence: 99%
“…The SLC is a 20-item measure tapping both the ' 'liking'' and ' "competence'' components of global self-esteem, and the SAQ is a 15-item measure tapping the respondent's self-perceived intelligence, social competence, artistic /musical ability, athleticism, and attractiveness; the certainty with which the respondent holds these five self-views; and the importance of these self-views to the respondent. Finally, targets completed the Activity Preferences Questionnaire (APQ; Surra & Longstreth, 1990), a 37-item measure that requires respondents to rate the extent to which they enjoy various activities (e.g., cleaning their rooms, going to a bar, playing board games, etc.). 2 Perceivers completed the same questionnaires as the targets but were instructed to "answer each questionnaire the way you think your partner would answer."…”
Section: Methodsmentioning
confidence: 99%
“…Situations with conflicting interests activate predictable thoughts and emotions (greed, fear), yield more active and differentiated cognition, information-seeking, and self-presentation ("Can Mary be trusted? "), and afford the expression of specific motives (cooperation vs. competition, trust vs. distrust) , Insko & Schopler 1998, Surra & Longstreth 1990, Van Lange 2000.TEMPORAL STRUCTURE Interactions and relationships are dynamic phenomena that typically mutate and evolve. Therefore, interdependence should be understood not only in terms of the immediate outcomes produced by specific combinations of behavior but also in terms of the future behaviors and outcomes that are made available (vs. eliminated) as a consequence of interaction (Kelley 1984b, Kelley et al 2002.…”
mentioning
confidence: 99%
“…Situations with conflicting interests activate predictable thoughts and emotions (greed, fear), yield more active and differentiated cognition, information-seeking, and self-presentation ("Can Mary be trusted? "), and afford the expression of specific motives (cooperation vs. competition, trust vs. distrust) , Insko & Schopler 1998, Surra & Longstreth 1990, Van Lange 2000.…”
mentioning
confidence: 99%
“…On the other hand, some research found regular differences of opinion (e.g. Gottman, 1994;Holmes, 1989;Surra and Longstreth, 1990). Conflicts also appear to be more prevalent among younger couples than older ones (Hinde, 1997).…”
Section: Types Of Decisions and Conflictsmentioning
confidence: 99%